Sustaining knowledge society: information seeking behaviour among rural dwellers in Sarawak / Aiza Johari ... [et al.] - Johari, Aiza; Rozaimie, Awang; Unin, Norseha; Mohd Jawi, Abdul Ismail (Faculty of Information Management, 2023)
Information seeking behaviour (ISB) includes activities or actions taken by a person in identifying information needs, searching and seeking for the needed information, as well as, the behaviour for selecting and using the information to satisfy the identified needs. This ISB study seeks to explore information seeking behaviour among rural dwellers in Sarawak. Their demographical differences, which focus on age and academic qualifications, were examined based on their information-searching behaviour for preferred reading, preferred source of information, preferred information channel or medium and information trustworthiness. By utilizing a cross-sectional quantitative survey method, a proportionate distribution of 2000 questionnaires were employed to match the number of populations at 22 rural locations, identified based on Sarawak administrative districts. This study found that academic qualification and age level have more significant differences in the way that the rural dwellers indicate their information needs, information-seeking and information behaviour. The findings also illustrate that the respondents are heavily dependent on information provided by trusted people (face-to-face), such as by schoolteachers, friends and families, religious people (the imam/priest), as well as, information from reliable sources including from public libraries and public talks or events. For a greater understanding of the information needs among rural communities, local authorities may recruit and train local volunteers to assist with rural library projects. Additionally, library authorities together with local authorities and government agencies can assist these rural dwellers to readily adopt new technologies, to ensure an efficient distribution and sharing of information, especially in the remote areas of Sarawak.